2012
DOI: 10.1051/0004-6361/201016422
|View full text |Cite
|
Sign up to set email alerts
|

Automatic spectral classification of stellar spectra with low signal-to-noise ratio using artificial neural networks

Abstract: Context. As part of a project aimed at deriving extinction-distances for thirty-five planetary nebulae, spectra of a few thousand stars were analyzed to determine their spectral type and luminosity class. Aims. We present here the automatic spectral classification process used to classify stellar spectra. This system can be used to classify any other stellar spectra with similar or higher signal-to-noise ratios. Methods. Spectral classification was performed using a system of artificial neural networks that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Bailer-Jones et al (1998) use a committee of neural networks and obtain 2.09 subclass error in the classification mode. Navarro et al (2012) set-up a two-stage classification system which is trained on spectral indices and outputs the spectral and luminosity class. Three networks in the first stage contain two hidden layers with 50 neurons in each layer.…”
Section: Classification Methodologymentioning
confidence: 99%
“…Bailer-Jones et al (1998) use a committee of neural networks and obtain 2.09 subclass error in the classification mode. Navarro et al (2012) set-up a two-stage classification system which is trained on spectral indices and outputs the spectral and luminosity class. Three networks in the first stage contain two hidden layers with 50 neurons in each layer.…”
Section: Classification Methodologymentioning
confidence: 99%
“…e automatic stellar spectral classification of big astronomical databases is a challenge that has been addressed by computational intelligence techniques; among them the Artificial Neural Networks (ANNs) have proven their effectiveness and accuracy [4][5][6][7][8][9][10]. Results found in the studies mentioned previously showed that, with the Artificial Neural Network approach, it is possible to classify spectra with S : N as low as 20 with errors in the classification process lower than 2 spectral subtypes; therefore, with the advent of massive astronomical databases, the automatic methods are clearly more necessary to extract and analyze the spectral information in a fast and accurate way, even when noise is a strong characteristic in the data.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most powerful advantages of ANNs are their capacity to handle large volumes of information, resistance to noise in the data as well as to the lack of data, and the capacity to reach an accuracy on the classification process similar to that of an expert [9]. Combined with the use of Artificial Neural Networks and other classifiers, dimensionality reduction methods as Principal Component Analysis (PCA), Isomap, and index measurement have been applied, in order to reduce the size of the input vector and extract the main features for classification [8,10,16]; in these works, the authors reported that dimensionality reduction methods are efficient to extract and retain the most useful information in the spectra and thus can be used in the classification process.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral Classification: In order to determine an accurate spectral classification of the stars near the line of sight of each of the PNe, we obtained the spectra of these stars at the WHT, using the LDSS2 multi-object spectrograph with a resolution of 6Å. To determine the spectral type of the stars in each field, we developed an Artificial Neural Network System which is able to classify spectra with signal to noise ratio (S/N) as low as 20 with an accuracy better than 2 spectral subtypes (Navarro 2005;Navarro et al 2011). The neural networks were trained with the measurement of 35 spectral lines that are sensitive to spectral type and luminosity class.…”
Section: Observationsmentioning
confidence: 99%